Dietary intake and nutritional status in patients with systemic sclerosis. Issue 10 (October 1992) - Lundberg, A C; Akesson, A; Akesson, B
Abstract : Oesophageal dysmotility and abnormalities of intestinal function are important manifestations in systemic sclerosis and may have a significant effect on nutrient absorption and nutritional status. In this study 30 patients with systemic sclerosis with symptoms from the gastrointestinal tract were compared with matched healthy control subjects with respect to nutrient intake (four day record), anthropometric measurements, and biochemical nutritional status. The intake of energy (8.1 and 8.4 MJ/day) and its distribution among nutrients did not differ between patients and control subjects, but the lower intake of dietary fibre among patients with systemic sclerosis suggests that they avoided food with a coarse structure, such as coarse bread. The intake of vegetables and fruit also tended to be lower among patients with systemic sclerosis. Half of the patients had a subnormal arm muscle circumference, and two patients also had a subnormal triceps skinfold thickness, indicating severe malnutrition. The concentration of ascorbic acid, alpha-tocopherol, carotene, selenium, and also the proportion of linoleic acid (18:2) in serum phosphatidylcholine was lower in patients than in control subjects.